A Bibliometric Analysis and Systematic Literature of Scopus Indexed Journals of Mathematical Creativity Assessment - Nadya Dewinda Agustin; Mohammad Syarif Sumantri; Arita Marini (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: Mathematical creativity plays a crucial role in enhancing the quality of life, resolving challenges, driving change, and improving the efficiency and effectiveness of systems. The objective of this study is to analyze publications from Scopus-indexed journals that investigate the effectiveness of techniques in estimating mathematical creativity. Method: This research is a literature review that utilizes bibliometric analysis in RStudio and the PRISMA technique. Results: This research emphasizes the efficacy of open-ended problem-solving and some frameworks in boosting mathematical creativity. It also uncovers the potential of augmented reality and cooperative learning methodologies in strengthening students' cognitive and creative abilities. Our in-depth study highlights the need for ongoing research and novel pedagogical practices to fully use the advantages of these techniques and instruments in promoting critical and creative thinking in mathematics education. Novelty: The uniqueness of this research lies in the development of a mathematical creativity instrument that integrates analogical and divergent thinking skills into a single measurement model. This instrument provides a more comprehensive assessment of creativity than conventional instruments that focus solely on mathematical knowledge.